HYDROGEOLOGICAL ENVIRONMENT AND GROUNDWATER OCCURRENCES OF THE ALLUVIAL AQUIFERS IN PARTS OF THE CENTRAL GANGA PLAIN, UTTAR PRADESH, INDIA - Umar R. (My University, 2006)
A detailed hydrogeological investigation was carried out in parts of the Central Ganga Plain, India, with the objective of assessing the aquifer framework and its resource potential. The area was studied because of its dual hydrogeological situation, that is water logging and soil salinization in the canal command areas and depletion of aquifers in the western part of the basin. A comprehensive investigation of the aquifer system between the Ganga River and Kali River revealed its lateral and vertical dimensions and hydrogeological characteristics. Moreover, study of the groundwater occurrences, movements and behaviour, in terms of water level fluctuation with time and space, confirms the coexistence of over exploitation as well as water logging in the area.
Keywords: INDIA; CENTRAL GANGA PLAIN; AQUIFER SYSTEM; HYDRAULIC PROPERTIES; GROUNDWATER FLOW